2015
DOI: 10.1111/all.12666
|View full text |Cite
|
Sign up to set email alerts
|

Position paper of the EAACI: food allergy due to immunological cross‐reactions with common inhalant allergens

Abstract: In older children, adolescents, and adults, a substantial part of all IgE-mediated food allergies is caused by cross-reacting allergenic structures shared by inhalants and foods. IgE stimulated by a cross-reactive inhalant allergen can result in diverse patterns of allergic reactions to various foods. Local, mild, or severe systemic reactions may occur already after the first consumption of a food containing a cross-reactive allergen. In clinical practice, clinically relevant sensitizations are elucidated by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
181
2
28

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(214 citation statements)
references
References 95 publications
3
181
2
28
Order By: Relevance
“…Алергія -це неадекватна реакція організму на різ-ні речовини, що виявляється при безпосередньому контакті з ними. Харчова алергія -це проблема, най-більш поширена останніми роками [1]. Існує багато різних опитувальників, що можуть бути використані для встановлення якості життя у хворих на харчову алергію та гастродуоденальну патологію.…”
Section: вступunclassified
“…Алергія -це неадекватна реакція організму на різ-ні речовини, що виявляється при безпосередньому контакті з ними. Харчова алергія -це проблема, най-більш поширена останніми роками [1]. Існує багато різних опитувальників, що можуть бути використані для встановлення якості життя у хворих на харчову алергію та гастродуоденальну патологію.…”
Section: вступunclassified
“…Therefore, snakin/GRP may represent a new diagnostic marker of PFAS in addition to other allergens such as Bet v 1-like proteins involved in the well-studied birch/apple syndrome. 9 Whether specific allergenic immunotherapy using a BP14-containing cypress pollen extract can reduce the food-related symptoms remains unknown for the moment and would deserve more investigations. With regard to allergy to Cupressaceae pollen, Inuo et al 10 reported that a specific allergenic immunotherapy performed with a Japanese cedar pollen extract led to a decrease in basophile activation to tomato in a patient with a cedar/tomato syndrome.…”
Section: To the Editormentioning
confidence: 99%
“…In individuals with known clinical allergy to a specific food, cross reactivity can occur when a novel protein has a high amino acid sequence homology to a known allergenic protein, epitope or component as is in the food causing the allergy . There are many examples of clinically relevant cross reacting proteins in the literature, such as Bet v 1, LTP, profilin and others (Hoffmann-Sommergruber and Mills, 2009;Werfel et al, 2015).…”
Section: Subject Selectionmentioning
confidence: 99%